Redescription of two parasitic feather mites sampled from the last two Crested Ibises, Nipponia nippon (Temminck, 1835) (Pelecaniformes: Threskiornithidae), lived in Japan - Waki, Tsukasa; Shimano, Satoshi (Zootaxa, 2022)
The objective of this paper is to redescribe two feather mites, Compressalges nipponiae Dubinin, 1950 (Caudiferidae) and Freyanopterolichus nipponiae Dubinin, 1953 (Kramerellidae), based on samples collected from the last two individuals of the Crested Ibis Nipponia nippon (Temminck, 1835) from the native Japanese populations, which had been extirpated in 2003. Our study provides detailed description of the leg and idiosomal chaetotaxy, and many morphological structures, which were missed or misinterpreted in the original publications.